Strategi Bimbingan Manasik Haji dalam Meningkatkan Keterampilan Jamaah Haji pada Kantor Kementerian Agama Kota Banda Aceh - Ridwan Ridwan (Tadabbur: Jurnal Peradaban Islam, 2022)
In the implementation of the Hajj and Umrah pilgrimages, surges or increases always occur in Indonesia every year, and are the cause of the emergence of a complex problem. there are many problems within the scope of hajj and umrah, such as the lack of a guiding role by the guide, resulting in the ignorance of the pilgrims about the Hajj and Umrah Organizing Law. The purpose of this study was to determine the Hajj ritual guidance strategy for the Office of the Ministry of Religion of the City of Banda Aceh and the factors that support and hinder the strategy of guidance for the Hajj rituals in improving the skills of pilgrims at the Office of the Ministry of Religion of the City of Banda Aceh. This research was conducted with a field study using a qualitative descriptive method. Data collection techniques were carried out through interviews, observation and documentation. The results of the study show that the Strategy for guidance on Hajj rituals of the Office of the Ministry of Religion of the City of Banda Aceh in improving the skills of pilgrims by implementing a management strategy which includes 4 stages, the first is planning (planning). The second is organizing, the third is actuating, the fourth is supervision. Factors that support the existence of competent Hajj ritual guides, Have a legal umbrella, availability of adequate facilities and infrastructure, Inhibiting factors, there is a profile of pilgrims whose education level is elementary school, there is an advanced age for pilgrims so that their physical condition decreases, and has an effect on the lack of concentration of pilgrims pilgrimage in the implementation of Hajj ritual guidance